FENOMENA DAKWAH DIGITAL DI KALANGAN SANTRI: SUATU ANALISIS ERA SWIPE DAN SCROLL - Fitriah Fitriah; Syafiin Mansur, Umu Hani, Rizka Najiyah, Muthia Rizky Nabila (Jurnal Komunikasi, 2025)
The development of digital technology has changed the paradigm of da'wah in Indonesia, including among students. The phenomenon of digital da'wah is characterized by the use of social media platforms such as YouTube, TikTok, Instagram, and podcasts, along with the culture of "swipe and scroll" in information consumption. This research aims to analyze the forms, patterns, motivations, strategies, and impacts of digital da'wah carried out by students in the digital era. The research method used is qualitative descriptive with data collection through digital content studies, namely the analysis of da'wah content produced and shared by students on various social media platforms. Thematic analysis was carried out to identify communication patterns, strategies, motivations, and impacts of digital da'wah. The results of the study show that students convey da'wah through visual, audio-visual, and interactive forms that are educational, persuasive, and inspiring. The motivation of digital da'wah students includes spiritual, social, and self-development, even though they face challenges such as popularity pressure, the risk of simplifying materials, and maintaining the value of sincerity. An eflective digital da'wah strategy includes understanding the audience's character, choosing the right media, presenting creative and communicative content, and strong digital literacy. The impact of digital da'wah for students and pesantren is positive and significant, including expanding the reach of da'wah, improving the competence of students, and strengthening the image of pesantren as adaptive institutions, while at the same time creating ethical and strategic challenges that require guidance so that da'wah remains relevant and meaningful